PENGARUH PROGRAM K3 (KESEHATAN DAN KESELAMATAN KERJA) TERHADAP PRODUKTIVITAS KERJA KARYAWAN (STUDI KASUS PT. WASKITA KARYA PERSERO. TBK SANGATTA) - Delsinasari, Adella; Saiful, Saiful; Riana, Ausy (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2025)
Most construction and building industries maximize productivity through labor and equipment. This increase will impact the number of workplace accidents, particularly in construction activities. Generally, an increase in workplace accidents will lead to a decrease in productivity. The construction and building industry is characterized by long working hours, a stressful work environment, and the use of high-risk equipment, particularly at PT. Waskita Karya. One approach is to increase employee productivity. The purpose of this study was to determine and analyze the effect of the Occupational Health and Safety (K3) Program on Employee Productivity at PT. Waskita Karya (Persero) Tbk, Sangatta. The analytical tool used was a quantitative method. Data analysis is the process of simplifying data into a form that is easier to read and interpret, or a method of processing data into information so that its characteristics are easily understood and useful for solving problems, especially those related to research. The results of the study, which examined the effect of occupational health and safety (K3) variables on employee productivity, revealed an R-square of 73.8%. This indicates that the company has provided facilities in the form of occupational health and safety (K3) for employees so that they feel safe working and can reduce the risk of work accidents and increase the comfort of the work environment so that employees feel protected while working. In addition, the results of the t-test that the t-count of 16.463 > t-table = 1.984 can be interpreted as health and safety at work have a significant effect on productivity.